2005
DOI: 10.1007/s00276-005-0325-8
|View full text |Cite
|
Sign up to set email alerts
|

The Muscular Branching Patterns of the Ulnar Nerve to the Flexor Carpi Ulnaris and Flexor Digitorum Profundus Muscles

Abstract: The branching pattern of the ulnar nerve in the forearm is of great importance in anterior transposition of the ulnar nerve for decompression after neuropathy of cubital tunnel syndrom and malformations resulting from distal end fractures of the humerus. In this study, 37 formalin-fixed forearms were used to demonstrate the muscular branching patterns from the main ulnar nerve to the flexor carpi ulnaris muscle (FCU) and ulnar part of the flexor digitorum profundus muscle (FDP). Eight branching patterns were f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 14 publications
1
24
0
Order By: Relevance
“…The MGA is the most widely discussed and studied of the 4 types of anastomoses. In our study the pooled prevalence of MGA was 19.5%, similar to the anatomical study by Marur et al 24 who reported a prevalence of 18.9%. Subgroup analysis according to type of study revealed that electrophysiological studies had a higher pooled prevalence of 23.5% when compared with the 16.4% in cadaver studies.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…The MGA is the most widely discussed and studied of the 4 types of anastomoses. In our study the pooled prevalence of MGA was 19.5%, similar to the anatomical study by Marur et al 24 who reported a prevalence of 18.9%. Subgroup analysis according to type of study revealed that electrophysiological studies had a higher pooled prevalence of 23.5% when compared with the 16.4% in cadaver studies.…”
Section: Discussionsupporting
confidence: 91%
“…A total of 6 studies ( n = 67 upper limbs) reported data on the position of the MGA with respect to the ulnar artery . In a majority of cases, the connection between the nerves was located posterior to the ulnar artery (89.8%, 95% CI, 74.9%–99.0%) rather than anterior (10.2%, 95% CI, 0.1%–25.1%; Cochran Q, P = 0.03; I‐squared = 58.7%, 95% CI, 0.0%–83.3%).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations